Proteomic Analysis of Proteins Engaged in α‐Methylene‐δ‐Lactone Cytotoxic Effects in Hormone‐Independent Breast Cancer MDA‐MB‐231 Cells. (1st July 2014) - Wyrebska, Anna; Pawlowska, Zofia; Gach, Katarzyna; Komorowski, Piotr; Protas, Anna; Walkowiak, Bogdan; Janecka, Anna
Abstract : A simple synthetic α ‐methylene‐ δ ‐lactone, 1‐ iso propyl‐2‐methylene‐1, 2‐dihydrobenzochromen‐3‐one, designated DL‐3, was shown previously to induce apoptosis and significantly suppress cell metastatic potential in MDA‐MB‐231 breast cancer cells. The mechanisms through which DL‐3 exerts its effects are poorly understood. The purpose of this study was to investigate the protein expression profiles in MDA‐MB‐231 cells exposed to the DL‐3 treatment. Using 2D differential gel electrophoresis, a set of eight differentially expressed proteins (spot intensities which showed ≥1.25‐fold change and statistical significance, p < 0.05, between the control and DL‐3‐treated group) were found and successfully identified by mass spectrometry (MALDI‐TOF/MS). The proteomic results revealed that the presence of DL‐3 in MDA‐MB‐231 cells led to the differential regulation of some proteins that are involved in the cell cycle progression, apoptosis, cytokinesis, modulation of transcription, cellular signaling, and vesicular trafficking. The function of other identified proteins is still unknown. Therefore, our data indicate new directions for the further studies of the pathways engaged in the anticancer action exerted by α ‐methylene‐ δ ‐lactones in cancer cells. Abstract : The protein expression profiles were investigated in MDA‐MB‐231 breast cancer cells exposed to a synthetic α‐methylene‐δ‐lactone, 1‐ iso propyl‐2‐methylene‐1, 2‐dihydrobenzochromen‐3‐one, designated DL‐3. Using the 2D gel electrophoresis, a set of eight differentially expressed proteins were found and successfully identified by mass spectrometry (MALDI‐TOF/MS). The proteomic results indicated new directions for the further studies of the pathways engaged in the anticancer action exerted by α‐methylene‐δ‐lactones in cancer cells.